2007
DOI: 10.1164/rccm.200611-1588oc
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Treatment of Mild to Moderate Obstructive Sleep Apnea Reduces Cardiovascular Risk

Abstract: OSA treatment was associated with a cardiovascular risk reduction of 64% independent from age and preexisting cardiovascular comorbidities. OSA treatment should be considered for primary and secondary cardiovascular prevention, even in milder OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(220 citation statements)
references
References 45 publications
8
196
1
9
Order By: Relevance
“…Continuous positive airway pressure (CPAP) is the primary treatment for obstructive sleep apnea (OSA) and has been proven to improve outcomes such as daytime sleepiness, cognitive performance, blood pressure, glucose control, cardiovascular status, quality of life and mortality [1][2][3][4][5][6] . Treatment efficacy is however limited by variable adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is the primary treatment for obstructive sleep apnea (OSA) and has been proven to improve outcomes such as daytime sleepiness, cognitive performance, blood pressure, glucose control, cardiovascular status, quality of life and mortality [1][2][3][4][5][6] . Treatment efficacy is however limited by variable adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is the treatment of choice for OSA (19)(20)(21)(22). CPAP has been shown to improve sleep architecture, decrease risk of MVAs (33)(34)(35), improve quality of life (23,36), and decrease neurocognitive and cardiovascular consequences associated with OSA (12,22,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Several consensus statements have examined the efficacy of CPAP in the treatment of OSA (22,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…Buchner et al 13 for example, showed that CPAP treatment of patients with OSA had reduced risk of cardiovascular event (non-fatal MI, acute coronary syndrome with revascularization, death because of MI ) by 64% in a group of 449 patients independent of age and coincident co-morbidities. In a similar fashion, Marin et al 14 described an increase in fatal events (OD 2.87) and nonfatal events in patients with untreated OSA.…”
Section: Discussionmentioning
confidence: 99%